The impact of exit strategy in Extended Public Works Programmes in Tzaneen Area, Limpopo Province - Gafane, Agnes Maphela (My University, 2011)
The study deals with the exit strategy impact within EPWP, WFW programme in Tzaneen area, Limpopo province. WFW programme employs contractors and workers for a short period of time and exit them out of the programme after skills transfer and training. In order to investigate the impact of exit strategy within the WFW programme, the researcher made use of different research techniques. The empirical data was collected on the basis of: a survey of 55 respondents, follow up interview with all respondents, and observation of the candidates who are due for exit. The major research findings clarify the selection and recruitment of workers and contractors in the programme, their training and skills development during the employment process, and finally, the exit achievements for poverty alleviation and further employability. It was recommended that exit strategy should be planned properly from the first day of employment, looking at the educational level of contractors and workers. The period of two years in the programme could be extended. In addition to training activities, a version of ABET programme could be implemented for them to improve their educational level. Exit strategy should be sustainable in such a way that the contractors and workers are able to improve their livelihood even after leaving the programme.
Thesis (M. Dev.) --University of Limpopo, 2011.
Keywords: Employee training; Job creation; 331.25729; Employees -- Training of -- South Africa; Job creation -- South Africa